Adaptation of the dynamic mechanical analysis to determine the gel point during the setting of liquid alkali silicates. Issue 6 (25th July 2019) - Hopp, Vanessa; Sax, Almuth; Helmus, Dominic; Quirmbach, Peter
Abstract: The gel point is one of the relevant parameters for the characterization of materials that undergo a sol‐to‐gel‐transition during their setting. A test method for its determination could be the Dynamic Mechanical Analysis, currently used in the field of polymer science. For the first time this measuring principle has been adapted to the group of liquid alkali silicates, thus verifying the possibility to describe their setting process. Three analytical methods for the determination of the gel point were studied with regard to their applicability and consistency for a compound alkali silicate system used as chemical hardener.